Descriptions of the nymphal stages of Gestroiella limnocoroides Montandon, 1897 (Hemiptera: Naucoridae) - Phan Thi Giang,; Truong Xuan Lam,; Ha Ngoc Linh,; Ryndevich Sergey,; Nguyen Quang Cuong, (Academia Journal of Biology, 2025)
Gestroiella limnocoroides Montandon, 1897, a species belonging to the subfamily Cheirochelinae has been recorded from Vietnam for the first time nearly 20 years ago. This study presents the first descriptions of the nymphal stages of the species. All five nymphal instars are described and illustrated in detail. Both adults and nymphs of G. limnocoroides were collected from vegetated stream margins in Vu Quang National Park, Ha Tinh province, where no other closely related species were observed. Each nymphal instar exhibits a head with a square-shaped ventral margin that is dark brown in color; a pronotum with a squarely concave anterior margin and a convex posterior margin that curves posteriorly; and a dorsal surface marked with alternating dark and light brown spots and two distinct black dots. Additionally, a morphometric analysis based on 22 morphological traits is provided for the nymphal stages.